ANALYSIS OF FACTORS INFLUENCING GENERATION Z'S PREFERENCE FOR GREEN FINANCE-BASED SHARIA INSURANCE PRODUCTS IN MEDAN CITY - Sonang Matua Siregar; Tri Inda Fadhila Rahma; Khairina Tambunan (Jurnal Asy-Syukriyyah, 2026)
The growing adoption of sustainable finance has influenced Generation Z's financial preferences, including the selection of sharia insurance products. However, limited studies have examined the mediating role of green finance in explaining this behavior. This study aims to analyze the effects of income and financial literacy on the selection of sharia insurance products through green finance among Generation Z in Medan City. A quantitative approach was employed using a survey of 103 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that income and financial literacy do not directly influence the selection of sharia insurance products. However, both variables significantly affect green finance, which, in turn, has a significant positive effect on the selection of sharia insurance products and mediates the relationships between income, financial literacy, and insurance selection. These findings highlight the importance of integrating sustainability values into sharia insurance strategies targeting Generation Z.